2005
DOI: 10.1111/j.1365-2095.2005.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth, feed utilization and health of Atlantic salmon Salmo salar L. fed genetically modified compared to non-modified commercial hybrid soybeans

Abstract: The present paper represents a part of a major scientific effort aiming to reveal possible effects, nutritional or health related, of genetically modified (GM) feed ingredients for Atlantic salmon. For 3 months groups of post-smolt Atlantic salmon were treated with diets holding 130 g kg 1 of the protein as soybean, one which contained 800 g kg )1 GM type RR (Roundup Ready ä ), and compared with a standard counterpart (commercial hybrid, not isogenic line) analysed to be non-GM (nGM), and again compared with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
67
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 47 publications
20
67
3
Order By: Relevance
“…These results are in agreement with previous studies on other species such as catfish [11], Atlantic salmon [12,14,20,21], and rainbow trout [13]. Similar results were also reported in swine [8], rat [22], and broiler [23].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…These results are in agreement with previous studies on other species such as catfish [11], Atlantic salmon [12,14,20,21], and rainbow trout [13]. Similar results were also reported in swine [8], rat [22], and broiler [23].…”
Section: Discussionsupporting
confidence: 95%
“…Feeding experiments with GM soybeans have been conducted in some species of animals including swine [8][9][10], catfish [11], Atlantic salmon [12], and rainbow trout [13]. From those studies, it is concluded that GM SBM is substantially equivalent to non-GM SBM.…”
Section: Introductionmentioning
confidence: 97%
“…This result is in agreement with previous studies with Atlantic salmon (Hemre et al, 1995;Heikkinen et al, 2006;Bakke-McKellep et al, 2007b), cod (Forde-Skjaervik et al, 2006), sea bass (Tibaldi et al, 2006), Egyptian sole (Bonaldo et al, 2006), channel catfish, Ictalurus punctatus (Evans et al, 2005), Japanese flounder (Kikuchi, 1999;Choi et al, 2004), Senegalese sole, Solea senegalensis (Aragão et al, 2003), and turbot, Scophthalmus maximus (Day and Gonzalez, 2000) where no significant changes in growth were detected over the trial periods.…”
Section: Discussionsupporting
confidence: 83%
“…The authors indicated that GM soy protein intake affected pancreas function, evidenced by the early acute PAP mRNA increased levels and pancreas cellular changes followed by recuperation of acinar cells after 30 days. Evaluating the GM soybean in Atlantic salmon diet, enlarged spleen and possible impaired spleen function as the number of smaller-sized red blood cells simultaneously increased were indicated (Hemre et al, 2005). The same authors (Sagstad et al, 2008) reported lower plasma triacylglycerol levels and a significantly larger spleen somatic index in fish groups fed GM soybean compared to groups fed non-GM soybean.…”
Section: Effects On Animal Health Of Gm Soybeanmentioning
confidence: 72%